Observations of movement and site fidelity of white-beaked dolphins (Lagenorhynchus albirostris) in Icelandic coastal waters using photo-identification - Bertulli, Chiara G.; Tetley, Michael J.; Magnusdottir, Edda E.; Rasmussen, Marianne H. (J. Cetacean Res. Manage., 2023)
The white-beaked dolphin (Lagenorhynchus albirostris) is the most commonly sighted delphinid species in Icelandic coastal waters. However, little is known about the species’ abundance, site fidelity and movements throughout its range. Photo-identification studies were conducted from April– October (2002–10) during whalewatching operations in Faxaflói and Skjálfandi bays on the southwest and northeast coasts of Iceland, respectively. Minimum abundance, annual site fidelity and movement between bays were calculated. A total of 154 and 52 individuals were identified in Faxaflói and Skjálfandi bays, respectively. The annual re-sighting rate was 21.4% in Faxaflói bay while only one individual was re-sighted in Skjálfandi bay (1.7%). A total of five dolphins (2.3%) were matched between Faxaflói and Skjálfandi bays with the period between re-sightings ranging from 272 to 821 days (mean 28.16 days, SD = 5.94). Low site fidelity rates observed likely signify a much larger home range than the present study area, into either other coastal or offshore zones, or alternatively may be explained by a large natural population size and/or the opportunistic nature of sampling during this study. Therefore, expansion of the study area is required. The matches between bays suggest that white-beaked dolphins inhabit a largescale coastal range of the Icelandic coast and can be considered highly mobile and transient possibly due to scarce and patchy resources. Alternatively it could be due to a large population size.